The systematization of the Canon Law of 1917 - Sacher, Andrzej (Prawo Kanoniczne, 2020)
In the article entitled The systematization of the Canon Law of 1917 the author presents the course of the discussion of the members of the Papal Commission for the Codification of Canon Law with regard to the systematization of the CIC 1917. The article is based on sources and presents an analysis of the preserved archives created in the course of the activities conducted by the above-mentioned commission and located in the repository of the Vatican Secret Archive.